2002
DOI: 10.1002/mrdd.10003
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of chorioamnionitis and cerebral palsy

Abstract: In a recent meta-analysis evaluating the relationship between chorioamnionitis and cerebral palsy, we found that chorioamnionitis is a risk factor for both cerebral palsy and cystic periventricular leukomalacia (cPVL). The current paper extends the meta-analysis by including studies published in the year 2000, and by further evaluating the causes of heterogeneity among individual study results. Using a random effects model, clinical chorioamnionitis was significantly associated with both cerebral palsy (RR 1.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
1
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(138 citation statements)
references
References 51 publications
3
126
1
6
Order By: Relevance
“…In fact, in Wu's meta-analysis, no two studies used the same definition of clinical chorioamnionitis. 41 We have no reason to think there would be differential misclassification between cases and controls, therefore, our risk estimates remain valid but of reduced magnitude. In addition, we underestimated the true prevalence of maternal infection because we could not assess infection that occurred outside the period of delivery.…”
Section: Discussionmentioning
confidence: 82%
“…In fact, in Wu's meta-analysis, no two studies used the same definition of clinical chorioamnionitis. 41 We have no reason to think there would be differential misclassification between cases and controls, therefore, our risk estimates remain valid but of reduced magnitude. In addition, we underestimated the true prevalence of maternal infection because we could not assess infection that occurred outside the period of delivery.…”
Section: Discussionmentioning
confidence: 82%
“…Intrauterine infection greatly increases the risk of periventricular leukomalacia (PVL) and cerebral palsy in premature infants and term infants (Grether and Nelson, 1997;Wu and Colford, 2000;Wu, 2002), and cytokines have been implicated in this association (Dammann and Leviton, 1997). Elevated levels of IL-6 in fetal cord blood and of IL-6 and IL-1b in amniotic fluid are associated with white matter lesions and cerebral palsy in premature infants (Yoon et al, 1996;Yoon et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Others, however, have reported that chorioamnionitis is an antecedent of echolucency (50). Virtually all placentas and umbilical cords that have fetal vasculitis also have inflammation of the membranes, but only approximately half of placentas with membrane inflammation have fetal vasculitis (21,51).…”
Section: Discussionmentioning
confidence: 99%